HISTORICAL STAGES OF CANADA’S NATIONAL STRATEGY FORMATION OF HEALTH PROMOTION OF THE POPULATION - Mokhoniok, Zoriana (Educological discourse, 2020)
Analysis of the current socio-cultural situation shows that health promotion and maintaining health of the nation are formed as one of the priority areas and values of statehood and public consciousness. The principal social, economic and cultural changes that have taken place in Ukraine in recent years necessitate a revision of approaches to the modernization of the domestic health care system and the promotion of a healthy lifestyle. The current coronavirus COVID-19 outbreak literally locked down the whole world and isolated various continents, peoples, nations and countries from each other. Therefore this situation with pandemic clearly demonstrated the unpreparedness of both our country and the world’s most powerful states to resist global epidemics, the vulnerability of national healthcare systems and shortcomings in the field of health promotion. The purpose of this article is to outline and describe the main stages of Canada’s national strategy formation of health promotion. The article identifies the essential characteristics of the phenomenon of "health promotion". Recently, the problem of human health and a healthy lifestyle and its formation has acquired a new understanding and significance. The analysis of scientific and pedagogical literature testifies to the multifaceted phenomenon of a healthy lifestyle. Canada was the first country in the world to pay attention to the need of maintaining and strengthening the health of the younger generation by promoting a healthy lifestyle. This country was one of the first in the world to recognize the need for government assistance and regulation of healthy lifestyles. Analyzing the scientific and pedagogical literature, we can identify three stages of Canada’s national strategy formation of health promotion. The tasks of further scientific research are a more detailed theoretical analysis of each of the above stages, the drafting of prognostic recommendations with the possibility of taking into account the strategies of health promotion in the reform processes in modern Ukraine.